The Influence of Transformational Leadership Style, Organizational Culture, Perception of Organizational Support on Hospital Employee Engagement: Pengaruh Gaya Kepemimpinan Transformasional, Budaya Organisasi, Persepsi Dukungan Organisasi Terhadap Employee Engagement Karyawan Rumah Sakit - Hidayah, Ika Nurul; Sari, Dewi Komala (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine the effect of transformational leadership style, organizational culture and perceptions of organizational support on employee engagement at Al-Islam H.M Mawardi Hospital employees. This research is a type of quantitative research with hypothesis testing. The sample used in this study were 107 respondents, namely employees of the Al-Islam Hospital H.M Mawardi Sidoarjo. The analytical tool used is multiple linear regression analysis, coefficient of determination (R2), partial correlation coefficient, t test, F test, and classical assumption test using SPSS version 18.0 application program. This primary data was obtained through a questionnaire whose measurements used a Likert scale which tested the validity and reliability of the data declared valid and reliable Al-Islam H.M Mawardi Hospital, Sidoarjo. The results of this study prove that transformational leadership style affects employee engagement, organizational culture affects employee engagement, perceptions of organizational support on employee engagement. Transformational leadership style, organizational culture, perceived organizational support simultaneously affect employee engagement.